2005
DOI: 10.1007/s10964-005-3211-0
|View full text |Cite
|
Sign up to set email alerts
|

Gender/Racial Differences in Jock Identity, Dating, and Adolescent Sexual Risk

Abstract: Despite recent declines in overall sexual activity, sexual risk-taking remains a substantial danger to US youth. Existing research points to athletic participation as a promising venue for reducing these risks. Linear regressions and multiple analyses of covariance were performed on a longitudinal sample of nearly 600 Western New York adolescents in order to examine gender-and race-specific relationships between "jock" identity and adolescent sexual risk-taking, including age of sexual onset, past-year and lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 45 publications
3
54
0
Order By: Relevance
“…A "jock" identity may place less emphasis on conformity to established norms and more emphasis on conformity to an ethic that combines elements of hegemonic masculinity, risk-taking, and personal exemption from ordinary rules. Miller and her colleagues have linked jock identity with problem drinking (Miller et al, 2003), sexual risk-taking (Miller et al, 2005), and peer violence (Miller et al, 2006). Each of those behaviors is clearly consistent with a culturally dominant vision of what it means to be a man in the United States (Connell, 1995;Sabo and Runfola, 1980).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…A "jock" identity may place less emphasis on conformity to established norms and more emphasis on conformity to an ethic that combines elements of hegemonic masculinity, risk-taking, and personal exemption from ordinary rules. Miller and her colleagues have linked jock identity with problem drinking (Miller et al, 2003), sexual risk-taking (Miller et al, 2005), and peer violence (Miller et al, 2006). Each of those behaviors is clearly consistent with a culturally dominant vision of what it means to be a man in the United States (Connell, 1995;Sabo and Runfola, 1980).…”
Section: Discussionmentioning
confidence: 90%
“…However, when required to choose a gender-blind version of one of five identities exemplified in a recent popular movie (i.e., jock, brain, princess, basket case, or criminal), most male athletes (69%) identified themselves as jocks but a far smaller proportion of female athletes (22%) chose jock as their primary identity. Miller et al 2005 also found that jock identity was disproportionately a male characteristic; among adolescents who reported two or more hours of athletic activity per week, 55% of boys and 33% of girls identified themselves as jocks, and among those who reported fewer than two hours of athletic activity, jocks comprised 36% of boys and 15% of girls. The correlation between athletic activity and jock identity was only .31, and was significant for white but not black male adolescents.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…An elite-type group was the leading group at school and comprised of members who generally were successful in academic and extracurricular activities, held a high opinion of themselves, and were high in both other-perceived and self-perceived social competence. The 10 studies that failed to delineate Elites included seven which subsumed Elites under an Athlete label (Downs & Rose, 1991;Eckert, 1983;Fordham & Ogbu, 1986;Kipke, Montgomery et al, 1997;Riester & Zucker, 1968;Urberg, 1992), and three studies that did not attempt to study Elites per se (they compared Athletes to Non-athletes, or Loners to Nonloners (Demuth, 2004;Miller et al, 2003Miller et al, , 2005). …”
Section: Resultsmentioning
confidence: 99%
“…One study (Ashmore et al, 2002) addressed college students. Six studies (Downs & Rose, 1991;Kipke, Montgomery, Simon, Unger, & Johnson, 1997;Kipke, Unger, O'Connor, Palmer, & LaFrance, 1997;Miller, Farrell, Barnes, Melnick, & Sabo, 2005;Miller et al, 2003;Sussman et al, 1999) targeted non-school based samples. Only three studies were conducted outside the U.S., all in school-based settings (Heaven, Ciarrochi, Vialle, & Cechavicuite, 2005;Michell, 1997;Thurlow, 2001).…”
Section: Subjectsmentioning
confidence: 99%